Resgate histórico do rio Praiado na comunidade Divino Espírito Santo: uma análise acerca da retirada das matas ciliares e suas consequências - SILVA, Ivancélia do Carmo Silva e (2021)
Riparian forests are the vegetation on the banks of the watercourses, they are of extreme importance for the maintenance of water resources, they have the role of protecting them from silting and erosion, they also prevent sediments from being carried inwards of the rivers compromising the quality and quantity of water. However, in search of more space for cattle breeding or agriculture, humans have been destroying the environment without realizing that many consequences will come as the scarcity of water and floods, silting and erosion of river banks. The focus of this work was to collect data for a historical rescue of the reality of the Prairie River and to provide information about the importance of maintaining riparian forests, how they can be recovered and preserved, and provide information on law 12.727 / 2012 of the forest code that governs the duty to maintain the PPAs. This data collection was carried out in four stages. The first was to carry out field surveys to obtain more accurate images and information. The second was to apply questionnaire 01 to 25 people in the community to collect data about their relationship with the river and how much they are informed about the forest laws and the duties of each one towards the nature, the third was the realization of a lecture on the riparian forests with the approach of subjects like preservation, recovery and functions of these forests, where it was counted on the presence of 35 people and lastly the application of questionnaire 02 to 21 people in the community and in this second interview was included some students of the local school, soon after elaborating a plan of recovery of the forests of an area in the banks of the river Praiado. However, the results obtained with the questionnaires and the lecture were very evident, the concept of riparian forest and its importance gained another meaning for them as a result of the awareness work carried out, since many did not understand what it was and what the function of the vegetation in the of the watercourses.